Development of a pH-Sensitive Nanoparticle via Self-Assembly of Fucoidan and Protamine for the Oral Delivery of Insulin - Hongying Cai; Fanxing Yong; Rui Li; Jianping Chen; Xiaofei Liu; Bingbing Song; Zhuo Wang; Qiaoli Zhao; Saiyi Zhong (MDPI AG, 2024)
Objectives: Oral insulin delivery has received much attention over the past 20 years due to its high compliance. The aim of this study is to prepare nanoparticles for the oral delivery of insulin; Methods: Fucoidan and protamine were used to prepare a pH-sensitive nanoparticle via self-assembly. The secondary structure and in vitro stability of the nanoparticles were characterized using FTIR, XRD, ITC, and TEM. the nanoparticles had a controlled release effect on insulin in simulated intestinal fluid. The pre-liminary therapeutic effect on high-fat-fed type 2 diabetic mice; Results: When the fucoidan/protamine mass ratio was 10:3 (w/w), the particle size and zeta potential were 140.83 ± 1.64 nm and −48.13 ± 0.61 mV.The encapsulation efficiency of insulin was 62.97 ± 0.59%. The preliminary therapeutic effect on type 2 diabetic mice showed that the fasting blood glucose of diabetic mice decreased from 10.28 ± 0.88 mmol/L to 9.22 ± 0.64 mmol/L, the area under the curve value of oral glucose tolerance test was reduced by 11.70%, and the insulin se-cretion of diabetic mice was increased by 13.3%; Conclusions: The nanoparticles were prepared successfully by self-assembly. The empty and insulin-loaded nanoparticles remained stable in simulated gastric fluid, and the nanoparticles had a controlled release effect on insulin in simulated intestinal fluid. Moreover, insulin-loaded nanoparticles could relieve on type 2 diabetic mice.